The Influence of Instagram Promotions and Free Shipping on Beauty Product Purchase Decisions in Palu City - Awanda Rabila; Sirajudin; Marwana (Universitas Muhammadiyah Palu, 2026)
This study aims to determine and analyze the influence of Instagram promotions and free shipping on purchasing decisions for Dobe Palu Shop beauty products. This study is a quantitative study. The study was conducted by distributing questionnaires to 96 people using multiple linear regression analysis methods. The results of the study indicate that partially the Instagram promotion variable has a positive and significant effect on purchasing decisions with a calculated T value of 6.178> T table 1.986 and a significance value of 0.000 <0.05. The free shipping variable also has a positive and significant effect on purchasing decisions with a calculated T value of 6.274> T table 1.986 and a significance value of 0.000 <0.05. Simultaneously, the calculated F value is 96.995> F table 3.09 with a significance value of 0.000 <0.05 and a coefficient value of 0.669 or 66.9%. so it is stated that the variation in purchasing decisions can be explained by the two independent variables and the remaining 31.9% is influenced by factors from other variables outside the scope of this study. This means that Instagram promotions and free shipping have a positive and significant effect on purchasing decisions for beauty products at Toko Dobe Palu